Clinical characteristics of preeclampsia in twin versus singleton pregnancies. (18th June 2022) - Avnon, Tomer; Ascher-Landsberg, Jessica; Yogev, Yariv; Many, Ariel
Abstract: Objective: We aimed to compare features of preeclampsia between twin and singleton pregnancies. Methods: In this retrospective case-control study, women with twin pregnancies who were diagnosed with preeclampsia were matched to singleton pregnancies controls. Results: Ninety-four women with twin gestation diagnosed with preeclampsia were compared to singleton pregnancies with preeclampsia. Twin pregnancies were diagnosed at an earlier mean gestational age (33.23 ± 7.32 vs 35.93 ± 3.52 weeks, p = .001), and had an earlier gestational age at delivery (35.05 ± 2.28 vs 36.31 ± 3.25 weeks, p = .002) in comparison to singleton pregnancies. Mean systolic blood pressure at diagnosis was lower (147.22 ± 14.62 vs 152.7 ± 15.22 mmHg, p = .013), and the rate of thrombocytopenia <100, 000 platelets/microliter, (17.02% vs 7.45%, p = .045) was higher in the twin preeclampsia group. A subanalysis for diagnosis prior to 34 weeks of gestation revealed that the rate of chronic hypertension was lower (3.03% vs 26.32%, p = .020), and the gestational age at delivery was higher (32.83 ± 2.16 weeks vs 31.02 ± 2.49, p = .008) among the twin preeclampsia group. In the prior to 34 weeks gestation preeclampsia subanalysis, less women in the twin group were hospitalized due to maternal indications (hypertension, ominous signs for PE, disturbed laboratory tests and suspicion for intra-hepatic cholestasis of pregnancies) in comparison to the singleton preeclampsia group (63.64% vs 89.47%, p = .028), while non-maternal/fetal indications (active labor, premature rupture of membranes, cervical dynamics, latent phase or gastroenteritis) for hospitalization were more common in the twin preeclampsia group (30.30% vs 0.00%). Conclusion: Preeclampsia in women with twin pregnancies is diagnosed at an earlier gestational age with lower level of hypertension and a higher rate of thrombocytopenia in comparison to singleton pregnancies.